Influence of the Inlet Valve Diameter, Container Volume, and of Horizontal Finning on the Rate of Filling a Container with UF6; Journal of Engineering Physics and Thermophysics; Vol. 92, iss. 2 - Orlov A. A. Aleksey Alekseevich; Tsimbalyuk A. F. Aleksandr Fedorovich; Malyugin R. V. Roman Vladislavovich; Leontjeva D. A. Darjya Andreevna (2019, 2019)
Title screen